Modelling of Vibrations of Overhead Line Conductors Assessment of the Technology (Technical Brochures,, 2018)
This brochure offers numerical models of wind-induced aeolian vibrations and sub-span oscillations of the conductors. It highlights what can be expected from numerical models regarding conductor vibrations. Assessment of the aeolian vibration condition of particular lines, with conductors whose mechanical properties are poorly defined, or with special terrain conditions, may require field measurements; Analytical methods based on the EBP and shaker-based technology can provide a useful tool to design damping systems for the protection of single conductors against aeolian vibrations This work reports the state of the art for professionals regarding aeolian vibrations and subspan oscillations modelling.